2017
DOI: 10.4103/0253-7176.203121
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Pilot Study of Brief Intervention versus Simple Advice for Women Tobacco Users in an Urban Community in India

Abstract: Aim:The study aimed to assess the efficacy of providing brief intervention (BI) for women tobacco users in a community-based setting.Methods:In this open-labeled randomized study, a representative sample of women (n = 100) from a community in East Delhi were screened using Alcohol, Smoking and Substance Involvement Screening Test. Eligible women were randomized to BI or simple advice (SA) arms. At baseline, they were assessed for tobacco use characteristics and severity of nicotine dependence using Fagerstrom'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 20 publications
(24 reference statements)
0
6
0
Order By: Relevance
“…Overall, the RR (CI) ranged from 0.87 (0.7, 1.09) to 3.84 (2.33, 6.33). The one case-control pilot study conducted by Jhanjee et al 25 showed an RR (CI) of 1.80 (0.77, 4.25) at the end of three months of treatment (Table I). Therefore, the trials suggested a benefit of behavioural interventions in SLT cessation.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Overall, the RR (CI) ranged from 0.87 (0.7, 1.09) to 3.84 (2.33, 6.33). The one case-control pilot study conducted by Jhanjee et al 25 showed an RR (CI) of 1.80 (0.77, 4.25) at the end of three months of treatment (Table I). Therefore, the trials suggested a benefit of behavioural interventions in SLT cessation.…”
Section: Resultsmentioning
confidence: 97%
“…Twenty randomized controlled trials (RCTs) (case-control studies) on behavioural interventions for SLT cessation were reported; sixteen were conducted in the USA78910111213141516171819202122, three in India232425 while only one study was reported from Sweden26. Most studies had majority of adult participants while three were conducted among the youth132024.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…First, a move away from the focus on tertiary-care for addictions is necessary, as it is not only expensive, but also has limited availability and access. Second, with most research in India being focused on BIs for tobacco use [ 76 78 ], expansion to other areas of addictions research is crucial. Third, there needs to be a move towards adoption and scaling up of contextually appropriate and evidence-based interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Health education and counseling enabled women of Mumbai in low socioeconomic status (SES) to quit SLT at one-year follow-up with the quit rate of 33.5% [ 32 ]. Subjects in the behavioral intervention group were two times more prone to ceasing tobacco use compared to individuals in the simple advice group, where in 94% of SLT users were from lower SES strata [ 33 ]. About 12.5% had undetectable cotinine at six months when behavior change intervention for SLT cessation was supported [ 34 ].…”
Section: Discussionmentioning
confidence: 99%